Lymphoproliferation in Inborn Errors of Immunity: The Eye Does Not See What the Mind Does Not Know - Sharma, Saniya; Pilania, Rakesh Kumar; Anjani, Gummadi; Sudhakar, Murugan; Arora, Kanika; Tyagi, Rahul; Dhaliwal, Manpreet; Vignesh, Pandiarajan; Rawat, Amit; Singh, Surjit (Frontiers in Immunology, 2022)
Inborn errors of immunity (IEIs) are a group of heterogeneous disorders characterized by a broad clinical spectrum of recurrent infections and immune dysregulation including autoimmunity and lymphoproliferation (LP). LP in the context of IEI may be the presenting feature of underlying immune disorder or may develop during the disease course. However, the correct diagnosis of LP in IEI as benign or malignant often poses a diagnostic dilemma due to the non-specific clinical features and overlapping morphological and immunophenotypic features which make it difficult to treat. There are morphological clues to LP associated with certain IEIs. A combination of ancillary techniques including EBV-associated markers, flow cytometry, and molecular assays may prove useful in establishing a correct diagnosis in an appropriate clinical setting. The present review attempts to provide comprehensive insight into benign and malignant LP, especially the pathogenesis, histological clues, diagnostic strategies, and treatment options in patients with IEIs.